PHYSICS LEARNING USING REAL AND VIRTUAL LABORATORY ACTIVITES TO IMPROVE STUDENT COMPETENCIES IN BOYLE-GAY LUSSACS LAW AND IDEAL GASES EQUATION - ROHANIYAH, ASSIFAA (Inovasi Pendidikan Fisika, 2017)
The aim of this research is to describe the implementation of learning, improvement of competence, and students response toward physics learning using real and virtual laboratory in Boyle-Gay Lussacs Law and ideal gases equation. Improved competencies include knowledge and skills. The type of research was used pre-experimental with one-group pretest-posttest design by using three experimental classes. The subjects of the study were students of class XI IPA 1, XI IPA 2, and XI IPA 3 in SMAN 4 Sidoarjo. Instruments used are observation sheet of learning implementation, pretest posttest of knowledge and skill, process skill assessment sheets, and student response questionnaire. Increased student competence was analyzed by paired t-test and gain score analysis. The results showed that (1) the implementation of learning was done very well; (2) students knowledge and skill competitiveness increased significantly in high category; (3) students response to learning through real and virtual laboratory activities got good category.   Key words: real laboratory, virtual laboratory, Boyle-Gay Lussacs Law and ideal gases equation.